Environmental assessment of a stream located in Novo Hamburgo, RS - Belem Machado, Aline; Zimmermann Prado Rodrigues, Gabriela; Gil de Souza, Fernanda; Linden, Rafael; Migliavacca Osorio, Daniela (Revista Geama, 2018)
The Luiz Rau stream is one of the main tributaries of the lower reaches of the Sinos River basin, and receives a large part of the city's domestic waste, being recognized by its typical odor and its dark coloration. Thus, the objective of the study was to evaluate the water quality of this water resource. For this, physical-chemical and microbiological analyzes of water were carried out, and in order to better support these results, the Rapid Habitat Assessment Protocol (RAP) was applied at the same sampling site. The results showed values of coliforms, BOD and OD above the limits established by current legislation. A high caffeine value was also identified in the collected sample, which characterizes the presence of domestic discharge in the water. The RAP revealed the presence of anthropic interference at the site, corroborating with the results obtained in the quantitative analysis of the sample. However, other studies are necessary to better evaluate the water quality of this stream.